Gender, poverty, and inequality: a brief history of feminist contributions in the field of international development - Kabeer, Naila (Gender & Development, 2015)
This paper provides a brief history of feminist contributions to the analysis of gender, poverty, and inequality in the field of international development. It draws out the continuous threads running through these contributions over the years, as the focus has moved from micro-level analysis to a concern with macro-level forces. It concludes with a brief note on some of the confusions and conflations that continue to bedevil attempts to explore the relationship between gender, poverty, and inequality.
Keywords: approches et analyses; cours; discipline; développement international; histoire et politique; intersectionnalité; inégalités; justice sociale; pauvreté; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; systèmes d'oppressions; thématiques; économie

Working women, caring men, and the family bank: Ideal gender relations after the Washington Consensus dans Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (Developing partnerships: gender, sexuality, and the reformed World Bank, 2009)
A critique of how the World Bank encourages gender norms, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations. By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world’s most influential development institution.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; inégalités; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences de la gestion; sud global; systèmes d'oppressions; thématiques; économie